Proceedings of the conference of the association of Southeast Asian Institutions of Higher Learning (ASAIHL) : International general conference on "The role of Universities in the Quest for Peace". (Makati City, Philippines : ASAIHL, 2004)
ASAIHL, is a non-governmental regional organization that has an aim to assist member institutions to strengthen themselves through mutual self-help to achieve distinction in teaching, research, and public service, thereby contributing to their respective nations and beyond.
Program of Activities -- Theme: The Role of Universities in the Quest for Peace : Makati Shangri-La Hotel -- Presentation of country Reports -- Session 1. Curricular and Co-Curricular Developments for Peace Education -- Session 2. Curricular and Co-Curricular Developments for Peace Education, Skills training in promoting a culture of Peace -- Session 3. Inter-Institutional Cooperation for Peace -- Values for peace, Values Enhancement for Peace -- Session 4. Community Projects for Peace (NGO&GO) , Interreligious Approaches for peace education.
Keywords: CONGRESSES